Implementation of the Brute Force Algorithm in the Design of Android-Based Thesis Catalogs (Knowbase : International Journal of Knowledge in Database, 2021)
This research was motivated by the confusion of students looking for title references for students' final assignments due to several obstacles, one of which was the lack of information about titles that had been done on their campus. The thesis catalog used in the library of the South Tapanuli Education Institute (IPTS) still uses printed media in one document in each department so that students have to take turns reading the catalog or students can directly look for theses one by one in the thesis cabinet or shelf and the current system is not yet running. using a database so as to allow the loss of the alumni thesis title data recap. So this is the background for the author to design a Thesis Catalog System by implementing a brute force algorithm in the process of searching for the title of the thesis. This thesis catalog system is a system that aims to facilitate the performance of library staff in inputting data, especially making it easier for students to find title references. The method that the author uses in this research is the development of R&D with the ADDIE model. In addition, the author also uses the SDLC development model while the model that the author uses in this study is the Waterfall model. The programming language used is the PHP language assisted by the MySQL database. Based on the results of the research that the author did, based on the validity test of 3 experts obtained a value of 0.80 Valid criteria, for the practicality test of 2 practitioners obtained a value of 0.889 very practical criteria and the effectiveness test of 10 students obtained a value of 0.871 very effective criteria, so that the value obtained proves that the thesis catalog system can help and is ready to use.